2004
DOI: 10.1017/s0958344004000710
|View full text |Cite
|
Sign up to set email alerts
|

What really makes students like a web site? What are the implications for designing web-based language learning sites?

Abstract: Faced with reduced numbers choosing to study foreign languages (as in England and Wales), strategies to create and maintain student interest need to be explored. One such strategy is to create 'taster' courses in languages, for potential university applicants. The findings presented arise from exploratory research, undertaken to inform the design of a selection of web-based taster courses for less widely taught languages. 687 school students, aged 14-18, were asked to identify a web site that they liked and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This implies that there was no statistically significant difference in the mean score between male and female schools teachers on the frequency use of multimedia for teaching in senior secondary schools in Kuje Area Council of Federal Capital Territory, Abuja. This result was relatively similar to Reference [18] which indicated no significant relationship between computer utilization and students' academic performance.…”
Section: H01supporting
confidence: 88%
See 2 more Smart Citations
“…This implies that there was no statistically significant difference in the mean score between male and female schools teachers on the frequency use of multimedia for teaching in senior secondary schools in Kuje Area Council of Federal Capital Territory, Abuja. This result was relatively similar to Reference [18] which indicated no significant relationship between computer utilization and students' academic performance.…”
Section: H01supporting
confidence: 88%
“…Despite the numerous benefits of multimedia in the educational sector, [17] highlighted some constraints to the use of multimedia. According to [17], these constraints were high price of multimedia facilities, lack of technical support for repairs and maintenance of multimedia facilities, inadequate multimedia manpower in schools, poor remuneration for teachers, poor attention of the government towards the development of ICT sector, inadequate funding of educational sector, insufficient teaching time, problem of over-dependence on fairly used computers, over-dependence of educational institutions on government for everything, limited/poor information infrastructure, large class size, lack of basic facilities, poor ICT policy/project implementation strategy, resistance to change by teachers and lack of interest by student [18]. Reference [19] stated that application of computer as an example of multimedia in education has contributed to the attainment of stated objectives in the teaching and learning process.…”
Section: Fig1 Examples Of Multimedia Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Users are able to benefit from the learning system of a website that is based on their preferences (Pituch & Lee, 2006). Website content and the practical use of the website may influence the users' perceptions (Hughes, Mcavinia & King, 2004;Sykes & Cohen, 2008). Users choose to use the online content as well as the website according to their preferences (Liu et al, 2011).…”
Section: Language Users' Preferencesmentioning
confidence: 99%
“…Thus previous studies on CALL evaluation have shown considerable interest in learners' and/or teachers' perceptions of English learning websites (Aly, 2008;Cheng, 2001;Hirata & Hirata, 2009;Kessler & Plakans, 2001;Kung & Chuo, 2002;M. Liu et al, 2008;Son, 2005Son, , 2008, the benefits and drawbacks of CALL materials/ programs, web-based language learning, and online language learning (Celik, 2012;Felix, 2001bFelix, , 2002Hughes, Mcavinia, & King, 2004;Murday, Ushida, & Chenoweth, 2008;Rosell-Aguilar, 2004;Wiebe & Kabata, 2010;F.-Y. Yang & Tsai, 2008), as well as learning autonomy in e-learning contexts (Chan & Kim, 2004;Lai & Gu, 2011).…”
Section: Significancementioning
confidence: 99%